Distinct Omicron longitudinal memory T cell profile and T cell receptor repertoire associated with COVID-19 hospitalisation - Markey, Gavin; McLaughlin, Joseph; McDaid, Darren; Lynch, Seodhna M.; English, Andrew; Alexander, H. Denis; Kelly, Martin; Bhavsar, Manav; McGilligan, Victoria; Zhang, Shu-Dong; Murray, Elaine K.; Rai, Taranjit Singh; et al. (Frontiers in Immunology, 2025)
SARS-CoV-2 has claimed more than 7 million lives worldwide and has been associated with prolonged inflammation, immune dysregulation and persistence of symptoms following severe infection. Understanding the T cell mediated immune response and factors impacting development and continuity of SARS-CoV-2 specific memory T cells is pivotal for developing better therapeutic and monitoring strategies for those most at risk from COVID-19. Here we present a comprehensive analysis of memory T cells in a convalescent cohort (n=20), three months post Omicron infection. Utilising flow cytometry to investigate CD4+CD45RO+ and CD8+CD45RO+ memory T cell IL-2 expression following Omicron (B.1.1.529/BA.1) peptide pool stimulation, alongside T cell receptor repertoire profiling and RNA-Seq analysis, we have identified several immunological features associated with hospitalised status. We observed that while there was no significant difference in median CD4+CD45RO+ IL-2+ and CD8+ CD45RO+ IL-2+ memory T cell count between subgroups, the hospitalised subgroup expressed significantly more IL-2 per cell following Omicron peptide pool exposure in the CD8+CD45RO+ population (p <0.03) and trended towards significance in CD4+CD45RO+ cells (p <0.06). T cell receptor repertoire analysis found that the non-hospitalised subgroup had a much higher number of circulating clonotypes, targeting a wider range of predominantly MHC-I epitopes across the SARS-CoV-2 genome. Several immunodominant epitopes, conserved between both subgroups, were observed, however hospitalised individuals were less likely to express putative HLA alleles responsible for pMHC presentation which may impact TCR affinity. We observed a bias towards shorter CDR3 segments in TCRβ repertoire analysis within the hospitalised subgroup, alongside lower rates of repertoire overlap in CDR3 sequences compared to the non-hospitalised subgroup. We found a significant proportion of TCRs targeted epitopes along the SARS-CoV-2 genome including non-structural proteins, responsible for viral replication and immune evasion. These findings highlight how the continuity of T cell based protective immunity is impacted by both the viral replication cycle of SARS-CoV-2 upon intracellular and innate immune responses, and HLA-type upon TCR affinity and clonotype formation. Our novel Epitope Target Analysis Pipeline (Epi-TAP) could prove beneficial in development of new therapeutic strategies through rapid identification of shared immunodominant epitopes across non-hospitalised and hospitalised subgroups.